(untitled) (Research, Society and Development, 2020)
Teaching mathematics in elementary education is a challenge for teachers and researchers. To overcome these methodological technical barriers, playfulness has been used. Playfulness is associated with dance, music and when playing, it is a powerful mechanism to increase students’ interest in some discipline or content. This methodology makes learning more fun and interesting, enabling the teaching of content in a light way. Due to its importance, this work has as an objective to use playfulness as a tool to aid the teaching of fractions. The research was carried out in a Municipal School, with 30 students in the 6th grade class, 13 of whom were male and 17 were female. An analysis of the theme was made through a questionnaire, the application of the game and an evaluation at the end of the activities. It was found that, with the insertion of games in classes, they became more dynamic and pleasurable, promoting greater interaction between students / material-manipulable / teacher, which contributed to an improvement in learning the content of fractions.